Glutathione Promotes Degradation and Metabolism of Residual Fungicides by Inducing UDP-Glycosyltransferase Genes in Tomato - Yu, Gaobo; Chen, Qiusen; Chen, Fengqiong; Liu, Hanlin; Lin, Jiaxin; Chen, Runan; Ren, Chunyuan; Wei, Jinpeng; Zhang, Yuxian; Yang, Fengjun; Sheng, Yunyan (Frontiers in Plant Science, 2022)
Reduced glutathione (GSH) is a key antioxidant, which plays a crucial role in the detoxification of xenobiotics in plants. In the present study, glutathione could reduce chlorothalonil (CHT) residues in tomatoes by inducing the expression of the UDP-glycosyltransferase (UGT) gene. In plants, UGT is an important glycosylation catalyst, which can respond to stresses in time by activating plant hormones and defense compounds. Given the importance of plant growth and development, the genome-wipe analyses of Arabidopsis and soybean samples have been carried out, though not on the tomato, which is a vital vegetable crop. In this study, we identified 143 UGT genes in the tomato that were unevenly distributed on 12 chromosomes and divided into 16 subgroups and found that a variety of plant hormones and stress response cis-elements were discovered in the promoter region of the SlUGT genes, indicating that the UGT genes were involved in several aspects of the tomato stress response. Transcriptome analysis and results of qRT-PCR showed that most SlUGT genes could be induced by CHT, and the expression of these genes was regulated by glutathione. In addition, we found that SlUGT genes could participate in plant detoxification through interaction with transcription factors. These findings further clarify the potential function of the UGT gene family in the detoxification of exogenous substances in tomatoes and provide valuable information for the future study of functional genomics of tomatoes.